[2,7-Dibutoxy-8-(4-fluorobenzoyl)naphthalen-1-yl](4-fluorophenyl)methanone - Hijikata, Daichi (International Union of Crystallography, 2012)
In the title compound, C(32)H(30)F(2)O(4), the benzene rings of the benzoyl groups make dihedral angles of 74.55 (6) and 74.39 (7)° with the naphthalene ring system. In the crystal, intra- and intermolecular C—H⋯π interactions are observed between the butoxy group and the aromatic rings. There are also C—H⋯F hydrogen bonds present that link the molecules into chains propagating along [010].